Phytochemical nanoencapsulation and microfluidics drive gene and tumor microenvironment modulation - Peñaherrera-Pazmiño, Ana Belen; Criollo, Mishell; Gonzalez-Pastor, Rebeca (Frontiers in Pharmacology, 2025)
Phytochemicals are plant-derived bioactive compounds with promising anticancer properties, but their clinical use is limited by poor solubility, instability, rapid metabolism, and restricted tumor penetration. Nanoencapsulation strategies address these barriers by enhancing bioavailability, stability, and tissue-specific delivery, thereby improving therapeutic efficacy and reducing systemic toxicity. This mini-review summarizes recent progress in nanoscale phytochemical delivery systems engineered for gene modulation and tumor microenvironment targeting, including lipid-based, polymeric, hybrid, and biogenic nanocarriers that improve biodistribution and enhance cellular uptake. Notably, the functional performance of nanoscale delivery systems depends on precisely controlled physicochemical characteristics. Consequently, microfluidics has emerged as a powerful tool to fine-tune and fabricate phytochemical-based nanocarriers in a reproducible manner. Beyond fabrication, microfluidic lab-on-a-chip platforms recreate physiological and tumor-specific microenvironments, providing dynamic, real-time assessment of drug transport, metabolism, and tumor–vascular interactions in biomimetic conditions that surpass conventional static models. These innovations expand mechanistic understanding and support more predictive preclinical evaluations. Remaining challenges include variability of natural sources, limited pharmacokinetic and toxicological data, and hurdles in scale-up and standardization. By integrating nanoscale engineering with microfluidic innovation, phytochemical-based nanomedicine is positioned to advance toward more effective, safer, and clinically translatable cancer therapies.